Influence of canopy pruning of Albizia procera on weed infestation in agrisilviculture system - Newaj, Ram; Singh, Traloki; Neekher, Shikha; Kumar, Upendra; Baronia, Chhavi (Indian Journal of Agroforestry, 2020)
A field experiment was conducted during 2006-08 at National Research Centre for Agroforestry, Jhansi (U.P.) India to elucidate the influence of canopy pruning of Albizia procera on weed infestation in agrisilviculture system. The experiment consisted of two crop sequences viz., blackgram [Vigna mungo (L.) Hepper]- mustard (Brassicajuncia L.Czern. & Coss.) and greengram (Vigna radiata Roxb.) - wheat (Triticum aestivum L. emend. Friori & Paol.), three pruning regimes viz., 70% canopy pruning, 50% canopy pruning and control (un-pruned trees). The experiment was conducted in split plot design with three replications. Among different pruning regimes, the weed population and dry weight of weeds was significantly (P â‰¤ 0.05) higher under 70% canopy pruning than 50% canopy pruning and control (un-pruned trees). Weed density and dry matter of weeds was higher in greengram at 30DAS but at harvest weed density and their dry matter were higher in blackgram during both the years. During rabi season, weed density was significantly higher in wheat than mustard at 30DAS but their dry weight was significantly higher in mustard than wheat at harvest stage.